Health system reform in peri-urban communities: an exploratory study of policy strategies towards healthcare worker reform in Epworth, Zimbabwe - Bernard Hope Taderera; Stephen James Heinrich Hendricks; Yogan Pillay (Taylor & Francis Group, 2016)
Background: Human resources for health (HRH) remains a critical challenge, according to the Kampala Declaration and Agenda for Global Action of 2008 and the 2030 Sustainable Development Agenda. Available literature on health system reforms does not provide a detailed narrative on strategies that have been used to reform HRH challenges in peri-urban communities. This study explores such strategies implemented in Epworth, Zimbabwe, during 2009-2014, and the implications these strategies might have on other peri-urban areas. Design: Qualitative and quantitative methods were used in an exploratory and cross-sectional design. Purposive sampling was used to select key informants, a sample of healthcare workers that participated in in-depth interviews and community members who took part in focus group discussions. Secondary data were collected through a documentary search. Qualitative data were analysed through thematic analysis. Quantitative secondary data were examined using descriptive statistics and then compared with qualitative data to reinforce analysis. Results: The HRH reform policy strategies that were identified included ministerial intervention; policy review; and revival of the human resource for health planning, financial planning, multi-sector collaboration, and community engagement. These had some positive effects; however, desired outcomes were undermined by financial, material, human resource, and social constraints. Conclusions: Despite constraints, the strategies helped revive the health delivery system in Epworth. In turn, this had a favourable outlook on post-2008 efforts by the Global Health Alliance towards healthcare worker reform and the 2030 Sustainable Development Agenda in peri-urban communities.